Internalization Of Islamic Character Education Values Through The Pancasila Student Profile Strengthening Project Rahmatan Lil ’Alamin (P5ra) At Madrasah Tsanawiyah Negeri Tebing Tinggi - Sitorus, Muhammad Rum; OK, Azizah Hanum; Mahariah, Mahariah (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the process of internalizing Islamic character education values through the Pancasila Rahmatan Lil 'Alamin (P5RA) Student Profile Strengthening Project at Madrasah Tsanawiyah Negeri Tebing Tinggi. This research is motivated by the phenomenon of low implementation of Islamic character among students even though the P5RA program has been implemented in various educational institutions. The research used a qualitative approach with phenomenological method. Data were obtained through interviews, observations, and documentation of the madrasah head, teachers, homeroom teachers, and students. The results showed that the internalized Islamic values include salimul 'akidah, shalihul 'ibadah, matinul khuluq, munazhzhamun fi syuunihi, and nafi'un lighoirihi. Internalization is carried out through contextual learning strategies, madrasah culture development, and extracurricular activities, with exemplary, habituation, and advice approaches. The main supporting factors for the success of internalization include the commitment of madrasah and parents, a religious environment, and adequate facilities. Meanwhile, the inhibiting factors include lack of understanding of the P5RA concept, time constraints, low student motivation, and lack of facilities and continuous evaluation. This study emphasizes the importance of collaboration, consistency of strategies, and strengthening evaluation in shaping students' Islamic character holistically and contextually.